Persistent dilemmas in zoster eye disease. Issue 1 (12th May 2015) - Cohen, Elisabeth J; Kessler, Jason
Abstract : Herpes zoster ophthalmicus (HZO) is a common, vision and potentially life-threatening disease caused by the reactivation of the varicella-zoster virus (VZV) in the distribution of the first division of cranial nerve V. Although the rate of herpes zoster increases with age, over half of the people with zoster in general, including HZO, are under age 60. In addition, over 90% of people with zoster are immunocompetent, even though the disease is more common and severe in immunocompromised patients. The incidence of zoster is increasing worldwide for unknown reasons. The epidemiology has not yet been impacted by the zoster vaccine (ZV). The lack of a strong recommendation by physicians for this vaccine is a major barrier to its use. An unresolved dilemma regards the optimum timing for this vaccine. In the USA, the current recommendation by the Centers for Disease Control and Prevention (CDC) is for eligible people age 60 and older, despite its greater efficacy in reducing the incidence of disease and Food and Drug Administration (FDA) approval for age 50–59. Although there is a consensus regarding use of acute high-dose oral antiviral treatment to reduce ocular complications, there is limited evidence for prolonged treatment. The rationale for a proposed randomised controlled trial (RCT) of suppressive antiviral treatment to reduce chronic eye disease and postherpetic neuralgia (PHN) includes evidence that zoster is followed by chronic active VZV infection and similarities between HZO and herpes simplex virus (HSV) eye infection, where this treatment is effective and is the standard of care.